Modalitas Visual Komunikasi Politik Iklan Pilkada Kota Bandung 2018 - Ferry Darmawan (MediaTor (Jurnal Komunikasi), 2018)
The banner of political advertising is a medium often used by prospective candidates who will fight in elections. As a medium of information, the installation of banners on crowded major arterial road is believed to be a powerful way to introduce themselves to the voting community. However, the existing phenomenon that political communication contained in the banner of political advertising tend to have the same pattern from year to year without any innovations. Using qualitative methods with social semiotics approach, this research revealed the visual modalities in banner ads of Bandung mayoral candidates for the period of 20182023.Modality is a social semiotics approach to the question of truth in the form of choices in expressing the message. Based on visual modalities analysis, the meaning of truth has low, medium, and high degree. The results of this study are (1) the Ad banners displayed website addresses and social media accounts to make it easier for audiences to seek additional information about prospective candidates (high modalities); (2) The ad banners displayed the headline of candidates and taglines (jargon) in accordance with the vision offered (high modalities); (3)the Ad banners displayed Bandung locality issues around happiness, beauty, comfort, until Bandung Creative (low modalities); (4) The target audience of the ad banners Bandung mayor candidates are students and college students (medium modality).